N-nitrodimethlyamine in natural and drinking water of high cancer incidence regions of Guangdong, China. (November 2016) - Liu, Xiuli; Cen, Kuang; Zhao, Lunshan; Chen, Yuan; Lun, Zhiying; Wu, Xuefang; Tian, Zhaoxue; Shi, Jinjin; Zhu, Xuetao; Wei, Junxiao; Wang, Ning; Chen, Wenwen
Abstract: The Guangdong province of China contains the most clearly described high-incidence of hepatocellular carcinoma (HCC) and nasopharyngeal carcinoma (NPC) areas in the world. The geographical heterogeneity of cancer incidence in the region suggests that many carcinogenic risk factors might be present in the regional geochemical environment. This paper presents the concentrations of a wide range of known carcinogens in two high cancer incidence areas in Guangdong and compared them to a low cancer incidence area in the same province. N -Nitrosamines, NO3 −, NO2 −, and ammonium were detected in groundwater, surface water, and drinking-water. The concentrations of the 7 trace metal and metalloid elements As, Cd, Ni, Cu, Pb, Zn, and Hg were determined in surface soil samples and all water samples. The results show that, compared with the guidelines or limit values for drinking-water quality in the world, the high cancer incidence areas have hazardous high levels of N -nitrodimethlyamine (NDMA) in all kinds of water. Oppositely, the low cancer incidence area has a safe low level of NDMA in water bodies. The levels of NO3 −, NO2 −, and ammonium in water have the same character, although they have different expression between the two high-risk areas. The distribution of the 7 tested trace elements in surface soil has no significant correlation with cancer incidence. On the other hand, high concentrations of carcinogenic N -Nitrosamines in drinking-water and natural water bodies were identified for the first time in the high NPC and HCC incidence area. Highlights: Detecting N -nitrosamines in water using GC/MS-SIM was used in natural-water in high cancer incidence area. High concentrations of N -nitrosamines in natural and drinking-water were identified in high NPC and HCC incidence area. The natural and drinking-water contains high concentration of N -nitrosamines, which increasing cancer incidence. The distribution of 7 tested metal elements in surface soil has no marked correlation with cancer incidence in this area.